A Practical Guide to the Manufacture of Sulfuric Acid, Oleums, and Sulfonating Agents - Ashar, Navin G.; Golwalkar, Kiran R.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
This critical volume provides practical insights on sulfuric acid and related plant design and on techniques to improve and enhance substantially the efficiency of an existing plant by means of small modifications. The book provides readers with a better understanding of the state-of-art in sulfuric acid manufacture as well as, importantly, in the manufacture of value-added products based on sulfur that are also associated with the manufacture of sulfuric acid. Overall, engineers and plant managers will be introduced to technologies for making their sulfuric acid enterprises more productive, remunerative, and environmentally friendly. A Practical Guide to the Manufacture of Sulfuric Acid, Oleums, and Sulfonating Agents covers sulfuric acid and derivative chemical plant details from the nuts-and-bolts level to a holistic perspective based on actual field experience. The book is indispensable to anyone involved in implementing a sulfuric acid or related chemical plant. This book also: Present a nuts-and-bolts to holistic guide on the manufacture of sulfuric acid and derivative products from technical and economic perspectives Includes novel innovations and rules of thumb to for optimal implementation of sulfuric acid and related chemical plants Provides comprehensive coverage of derivative products in sulfuric acid manufacture with detailed process descriptions Focuses attention through the book on practical design, co-generation of power, and operation parameters Outlines strategies on how to improve efficiencies in existing chemical plants with small modifications.
Current Status of Manufacture of Sulfuric Acid -- Sulfuric Acid Plant with Co-Generation of Power -- Sulphonating Agents and Derivatives based on Sulfuric Acid -- Innovations / Modifications in Technology -- Equipments Required for the Manufacture of Sulfuric Acid, Oleums and Liquid Sulphur Trioxide -- Materials of Construction of Main Equipments -- Safety Precautions -- Economic Considerations -- Future Developments --         Cold Process of Manufacturing Sulfuric Acid and Sulphonating Agents Patented by NEAT -- Storage, Handling and Properties of Sulphur, Sulfuric Acid, oleum and Liquid Sulphur Trioxide.           .
Keywords: Chemical engineering; Industrial engineering; Production engineering; Quality control; Reliability; Industrial safety; Facility management; Manufactures; Industrial Chemistry/Chemical Engineering; Industrial and Production Engineering; Quality Control, Reliability, Safety and Risk; Facility Management; Manufacturing, Machines, Tools, Processes